European codes of contemporary Ukrainian symbolism - S. P. Stoian, (Ukrainian Cultural Studies, 2020)
The article analyzes the specifics of contemporary Ukrainian symbolism in visual art in the context of a relationship with the European tradition. By drawing parallels between contemporary works by Ukrainian authors and symbolic images created in different historical periods of European culture from ancient times to nowadays, their deep kinship in their motives and meanings is demonstrated. This indicates that modern Ukrainian symbolism, on the one hand, is organically included in the European tradition, and on the other hand, contains unique, authentic features inherent in Ukrainian culture. Numerous works by contemporary Ukrainian authors, close to the idea of creating images, far from the principles of realism, images. It always hides multilayered, undiscovered meanings, testifies to the significant relevance of symbolism in contemporary art. At this stage of development, it demonstrates a crisis of form and radical conceptuality, in contrast to which artists are beginning to develop an interest in deeper, meaningful and multi-vector artistic images.It is noted that human is immersed in the world of symbols from birth, and it is this ability to symbolize even in primitive times begins to distinguish it from the animal world, because only human consciousness can create a symbolic space of culture. Art is also born in the bosom of symbolism because even the first rock paintings contain symbolic and mythological meanings. After all, man can see in the image of a tree, not just a plant that is a source of food or shelter, but a symbol of the universe, which combines three levels of the universe: underground, earthly and celestial.Symbolism is a much broader phenomenon than just an artistic direction, because the desire to generate symbolic images in art was present in all periods of human development, retreating to the periphery in times of powerful rationalization of culture and returning to the forefront of appealing to transcendent, irrational, unconscious of our existence.Only by conducting a thorough analysis of this phenomenon from the birth of art in primitive times, going through all stages of development of European culture, we can fully understand the origins, specifics and relationship of modern Ukrainian symbolism with European tradition, as well as its authenticity and originality. It distinguishes the phenomenon from all that has already been created in the space of visual art.
Keywords: symbolism, symbol, associative symbolism, image, artist, contemporary Ukrainian art